A polyhedral supramolecular system of endocyclic crystalline organic nanostructures: the case of triptycenes1. Issue 6 (14th February 2015) - Yang, Su-Hui; Lin, Zong-Qiong; Shi, Nai-En; Jin, Ling-Zhi; Yu, Meng-Na; Xie, Ling-Hai; Yi, Ming-Dong; Huang, Wei
<x xml:space="preserve">Abstract</x> Triptycene crystals with polyhedral or sheet-like shapes have been obtained in presence of surfactants and coincide with the simulated equilibrium shape.